The Effectiveness of ESG and Sustainability on Luxury Brand - Jin, Yongji (Transactions on Economics, Business and Management Research, 2024)
This study examines the impact of sustainability and environmental, social, and governance (ESG) concerns on luxury businesses, focusing specifically on Prada’s recent pledge to the United Nations Global Compact (UNGC). With the increasing urgency of global environmental challenges, luxury firms are under mounting pressure to embrace sustainable practices. The analysis examines Prada’s endeavors and their impact on the perception of the brand, customer loyalty, and financial results. The findings demonstrate that Prada’s commitment to ESG principles enhances its reputation, fosters customer confidence, and enhances its competitiveness in the market. The article demonstrates that the utilization of sustainable techniques not only aligns with ethical principles but also confers a competitive advantage to luxury firms. Firms such as Prada may more effectively navigate the obstacles posed by a rapidly evolving market if they adhere to sustainability objectives. In conclusion, the report asserts that adopting sustainability is crucial for achieving long-term success, enabling luxury firms to flourish while simultaneously making a positive impact on society and the environment.